Interpregnancy Changes in Maternal Weight and Body Mass Index - Crosby, David A.; Collins, Martha; O'Higgins, Amy; Mullaney, Laura; Farah, Nadine; Turner, Michael J. (American Journal of Perinatology, 2015)
Objective This longitudinal study compared changes in maternal weight and body mass index (BMI) in early pregnancy in the time interval between when a woman first attended for antenatal care with her first child and when she next attended for antenatal care.Study Design We studied women with a singleton pregnancy who delivered their first baby weighing ≥ 500 g in 2009 and who attended again for antenatal care with an ongoing pregnancy before January 1, 2012. Maternal weight and height were measured before 18 weeks' gestation in both pregnancies and BMI was calculated.Results Of the 3,284 primigravidas, the mean weight at the first visit in 2009 was 66.4 kg (standard deviation [SD] 12.7). The mean BMI was 24.5 kg/m2 (SD 4.6), and 11.3% (n = 370) were obese. Of the 3,284 women, 1,220 (37.1%) re-attended for antenatal care before 2012 after sonographic confirmation of an ongoing pregnancy. Of the 1,220 women who re-attended, 788 (64.6%) had gained weight (mean 4.6 kg [SD 3.9]), 402 (33%) had lost weight (mean 3 kg [SD 2.9]), and 30 (2.4%) had maintained their weight.Conclusion The birth of a first baby was associated with an increase in maternal weight in two-thirds of women when they next attended for antenatal care.
Keywords: maternal obesity; body mass index; interpregnancy weight gain